LAGU TIAS DALAM UPACARA PERNIKAHAN ADAT SIMALUNGUN DI DESA BANGUN PURBA (STUDI KAJIAN, BENTUK PENYAJIAN, FUNGSI DAN MAKNA LAGU) - Oktavianus, Eko Putra (Grenek: Jurnal Seni Musik, 2017)
"Songs Tias in Simalungun traditionalwedding ceremony in the village bangun purba (Studies of studies, forms ofpresentation, function and meaning of the song). This study aims to find outabout the song tias of form of presentation, function and meaning of the song inthe wake of early marriage ceremonies. This study is based on a theoreticalfoundation to explain the meaning assessment form, function and meaning of thesong. This research was conducted in the village bangun purba, during thewedding ceremony Simalungun. Data collected through literature study,observation, interviews, and documentation. This research was seen at thebeginning of the event to completion, with the aim of seeing the form ofpresentation, function and meaning of the song in the traditional Simalungun. Thefunction of this song was made to entertain the "boru" who come to the party"Tondong" which was performed during traditional wedding ceremonySimalungun wherever they are, including in the village bangun purba. And at thesame time see how the lives of people in the village get up early, and some clansin the area woke up early. This song has a meaning about a boy who had changedwhen he married them. The song is sung by a singer in the show, which isaccompanied by some traditional musical instruments Simalungun